Hate U Give Announcement Brochure - Kansas State University, K-State First (My University, 2018)
An announcement advertising "The Hate U Give" was selected as the 2018-2019 K-State Book Network common book. Sections include: synopsis, the book's awards, key themes, KSBN programming partners, and additional resources.
Keywords: Hate U Give, The; Events; Engagement; Common reading program; First-year experience program; Promotional materials; Promotional materials